Optimal metabolic regulation of the mammalian heart Na+/Ca2+ exchanger requires a spacial arrangements with a PtdIns(4)-5kinase - Forcato, Diego Oscar (2010)
In inside-out bovine heart sarcolemmal vesicles, p-chloromercuribenzenesulfonate (PCMBS) and n-ethylmaleimide (NEM) fully inhibited MgATP up-regulation of the Na+/Ca2+ exchanger (NCX1) and abolished the MgATP-dependent PtdIns-4,5P2 increase in the NCX1-PtdIns-4,5P2 complex; in addition, these compounds markedly reduced the activity of the PtdIns(4)-5kinase. After PCMBS or NEM treatment, addition of dithiothreitol (DTT) restored a large fraction of the MgATP stimulation of the exchange fluxes and almost fully restored PtdIns(4)-5kinase activity; however, in contrast to PCMBS, the effects of NEM did not seem related to the alkylation of protein SH groups. By itself DTT had no effect on the synthesis of PtdIns-4,5P2 but affected MgATP stimulation of NCX1: moderate inhibition at 1 mM MgATP and 1 µM Ca2+ and full inhibition at 0.25 mM MgATP and 0.2 µM Ca2+. In addition, DDT prevented coimmunoprecipitation of NCX1 and PtdIns(4)-5kinase. These results indicate that, for a proper MgATP up-regulation of NCX1, the enzyme responsible for PtdIns-4,5P2 synthesis must be (i) functionally competent, and (ii) set in the NCX1 microenvironment closely associated to the exchanger. This kind of supramolecular structure is needed to optimize binding of the newly synthesized PtdIns-4,5P2 to its target region in the exchanger protein.